USING VMWARE VSPHERE HYPERVISOR ESXI 6.5.0 FOR VIRTUALIZATION OF THE OPERATING SYSTEM KALI LINUX (64- BIT) FOR EDUCATIONAL PURPOSES IN THE FACULTY OF TECHNICAL SCIENCES: USING VMWARE VSPHERE HYPERVISOR ESXI 6.5.0 FOR VIRTUALIZATION OF THE OPERATING SYSTEM KALI LINUX (64- BIT) FOR EDUCATIONAL PURPOSES IN THE FACULTY OF TECHNICAL SCIENCES - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper using VMware vSphere hypervisor ESXi 6.5.0 for virtualization of the operating system Kali Linux (64-bit) for educational purposes in the Faculty of Technical Sciences is made.